Sistem Pendukung Keputusan Rekrutmen Karyawan Baru Menggunakan Metode Profile Matching Berbasis Web (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Recruitment is the main task of the human resources department to find qualified candidates for open positions in a company or organization. The problem that is often faced by companies during recruitment is the difficulty in determining applicants who meet the criteria. A decision support system is defined as a system that helps a manager's work to overcome problems by providing data for selected decisions. The decision support system has a decision support method that is the profile matching method.The results of research that has carried out the profile matching method for recruiting new employees are carried out by comparing the input value with the company's target value so that the difference in GAP can be known. Then weighting is carried out on each aspect of the existing criteria after the GAP value is known. To determine the total value, the core factor and secondary factor are grouped based on the weighting results. With the results of the total value then ranking is carried out to obtain the final result.